`f(x)= ax^3 + bx^2 + cx + d`

f(0)= 0

==> d = 0

f(2)= 4

==> 8a + 4b + 2c = 4

==> 4a + 2b + c = 2 .............(1)

`f'(x)= 3ax^2 + 2bx + c`

f'(2)= 0

==> 12a + 4b + c = 0...........(2)

8a...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f(x)= ax^3 + bx^2 + cx + d`

f(0)= 0

==> d = 0

f(2)= 4

==> 8a + 4b + 2c = 4

==> 4a + 2b + c = 2 .............(1)

`f'(x)= 3ax^2 + 2bx + c`

f'(2)= 0

==> 12a + 4b + c = 0...........(2)

8a + 2b = -2

4a + b = -1 ..................(3)

f''(x)= 6ax + 2b

f''(0)= 0

==> b = 0

4a = -1

==> `a = -1/4`

`` ==> 4a + c = 2

==> -1 + c = 2

==> c = 3

`==gt f(x)= (-1/4)x^3 + 3x` `==gt a = -1/4 ==gt b= 0 ==gt c = 3 ==gt d = 0`

``